2016
DOI: 10.2500/ajra.2016.30.4354
|View full text |Cite
|
Sign up to set email alerts
|

Do Probiotics have a role in the Treatment of Allergic Rhinitis? A Comprehensive Systematic Review and Metaanalysis

Abstract: Despite high variability among the studies, synthesis of available data provided significant evidence of beneficial clinical and immunologic effects of probiotics in the treatment of AR, especially with seasonal AR and LP-33 strains. With the rising pool of studies, the most promising strains in specific allergies can be revealed and adjuvant therapy with probiotics can be recommended for the treatment of AR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
80
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(90 citation statements)
references
References 66 publications
(179 reference statements)
4
80
0
1
Order By: Relevance
“…59 Jerzynska et al 59 observed a decrease in symptom-medication score in all groups treated with SLIT. 59 They also demonstrated a significant increase of CD4+CD25+Fox3+ cells in the children receiving SLIT with L rhamnosus compared with children treated with SLIT and vitamin D. 59 A systemic review of the probiotics in the treatment of AR by G€ uvenç et al 60 concluded that significant evidence suggests beneficial clinical and immunologic effects of probiotics. 60 The previously described probiotic clinical trials relied on oral dosing, and research into direct nasal probiotics is scarce.…”
Section: Probiotics In Perennial and Seasonal Allergic Rhinitismentioning
confidence: 99%
“…59 Jerzynska et al 59 observed a decrease in symptom-medication score in all groups treated with SLIT. 59 They also demonstrated a significant increase of CD4+CD25+Fox3+ cells in the children receiving SLIT with L rhamnosus compared with children treated with SLIT and vitamin D. 59 A systemic review of the probiotics in the treatment of AR by G€ uvenç et al 60 concluded that significant evidence suggests beneficial clinical and immunologic effects of probiotics. 60 The previously described probiotic clinical trials relied on oral dosing, and research into direct nasal probiotics is scarce.…”
Section: Probiotics In Perennial and Seasonal Allergic Rhinitismentioning
confidence: 99%
“…In the current study, a population of MCp in the BM of healthy adults was identified, which was more frequent, and had lower surface expression of integrin β7 than the recently described MCp population in the blood. 3 Integrin β7 is required for transmigration of mouse MCp into the lung. 4 Thus, we speculate that integrin β7 is upregulated on the human MCp upon release from the BM in preparation for their transmigration from the blood to the peripheral tissues.…”
Section: Demonstration Of Human Mast Cell Progenitors In the Bone Marrowmentioning
confidence: 99%
“…QoL was significantly better in a sub-analysis of the Lp-33 lactobacillus strain. However, total nasal and ocular qualityof-life scores were similar to placebo (Table 3) [73]. Conversely, in a meta-analysis of 1,919 patients the positive effect of probiotics on Rhinitis Quality of Life (RQLQ) scores, was significant (SMD: −2.23; 95% CI: −4.07, −0.40) though there was no effect on Rhinitis Total Symptom Scores (RTSS) (SMD −0.36; (95% CI: −0.83, 0.10) (…”
Section: Allergic Rhinitismentioning
confidence: 86%